Quantification of the Number of Steps in a School Recess by Means of Smart Bands: Proposal of Referential Values for Children and Adolescents - Jose Sulla-Torres; Rubén Vidal-Espinoza; Christopher Avendaño Llanque; Alexander Calla Gamboa; Manuel Zúñiga Carnero; Marco Cossio-Bolaños; Rossana Gomez-Campos (MDPI AG, 2023)
(1) Background: Regular physical activity has multiple benefits. Therefore, school recess is a key tool to provide opportunities for schoolchildren to engage in extracurricular physical activity, have fun, play and interact with their peers. The aim is to provide reference data to quantify the number of steps that children and adolescents perform in a school recess using smart bands according to age range and sex. (2) Method: A descriptive cross-sectional study was carried out in 494 schoolchildren aged 6 to 17 years (292 males and 202 females). Weight, standing height and waist circumference (WC) were evaluated. The body mass index (BMI) was calculated. The quantification of the number of steps during school recess was performed using a smart band. (3) Results: Percentiles were constructed for the number of steps (number of steps/recess). The cut-off points considered were <p25 (below average), p25 to p75 (average) and >p75 (above average). The median values in both sexes decreased as the age range increased. Youth who walked fewer steps during recess (<p25: below average) had elevated BMI and WC values relative to those who walked within average and above average. (4) Conclusion: The number of steps taken by schoolchildren during school recess decreases drastically with advancing age. The proposed reference values can be used to categorize schoolchildren according to the number of steps taken and to compare them among their peers. The results suggest their use and application in schools as a way of achieving the minimum physical activity recommendations.